KARAKTERISTIK PAPAN PARTIKEL DARI AMPAS SAGU DAN PEREKAT ASAM SITRAT BERDASARKAN KERAPATAN PAPAN - Lestari,, Maya; Setyawati, Dina (JURNAL HUTAN LESTARI, 2018)
This research aimed to analyze the characteristic ofÂ  particleboard from characteristics of dregs sago and citric acid adhesive based on board density. The research was conducted at Wood Workshop Laboratory, Wood Processing Laboratory, Faculty of Forestry, Tanjungpura University and Laboratory of PT. Duta Pertiwi Nusantara Pontianak. Citric acid adhesive was used with a concentration of 20 % based on the dry weight of sago dregs. The board sample target density where 0,5 gr/cm3, 0,6 gr/cm3, 0,7 gr/cm3. The board sampels were tested by JIS A 5908 - 2003 Type 8. The particleboard was 30 cm x 30 cm x 1 cm in hot pressure with temperature 1800c at 25 kgf/cm2. The research result showed that all density value and water content of particleboard here fullfil the JIS A 5908 - 2003 Type 8 standard. The best particleboard in this research was a board with 0,7 gr/cm3 density.Keywords: Citric Acid, Density, Dregs of Sago, Particleboard.